Clinical features of the course of Hirschsprung’s disease in newborns and infants with consideration of the extent of colonic aganglionosis - V.P. Prytula; O.O. Kurtash; V.F. Rybalchenko; S.F. Hussaini (Український журнал Перинатологія і педіатрія)
The clinical course of Hirschsprung’s disease (HD) in newborns and infants depends on the extent of сolonic aganglionosis, the age of patient, the presence of associated malformations and complications.